The Classification of Consumer Spending on OFD Platforms using Behavior Analysis - Tiara Ramadhani; Yuni Ros Bangun (Jurnal Manajemen Teknologi, 2023)
Abstract. This study investigated a problem associated with the COVID-19 pandemic, which caused Indonesia to enter an economic recession in the second and third quarters of 2020. In particular, the MSME industry was most greatly affected by the recession (LIPI, 2020). As a result of the pandemic, people were forced to conduct activities online in order to minimize the spread of the virus. Data from the Economic Creative Agency show that 60% of culinary MSMEs in Indonesia were adversely affected by the COVID-19 pandemic. In addition, the high competition among merchants, especially those in the culinary MSME sector, has forced businesses to transform and adapt to the changing situation. Ever since the COVID-19 pandemic, Online Food Delivery (OFD) platforms have become increasingly popular among the public. Thus, in order for MSMEs to continue innovating to maintain the stability of their business, this study uses behavior analysis to identify and segment consumers using OFD services. This study surveyed 100 OFD consumers in Jakarta using a questionnaire. The data were then analyzed using a decision tree model. The results revealed that there were five variables that greatly influenced an OFD consumer's spending: willingness to pay, purchase frequency, region of residence, factors that affect their preferred choice of merchant, and the type of merchant. The optimal decision tree model classified OFD consumer behavior into seven nodes, each with unique characteristics. These results helped to characterize and classify OFD consumer behaviors, allowing restaurants to maintain the profitability of their business by utilizing this information to better understand consumer needs as well as improve their decision-making processes.Keywords: Behavior, business transformation, consumer, online food delivery (ofd), decision treeAbstrak. Penelitian ini dilakukan untuk menganalisa permasalahan yang bersumber dari pandemi Covid-19 yang menyebabkan Indonesia mengalami resesi ekonomi pada kuartal kedua dan ketiga tahun 2020 yang membuat industri UKM terkena dampak terbesar selama pandemi (LIPI, 2020). Sehingga masyarakat melakukan aktivitas secara online guna meminimalisir penyebaran virus. Berdasarkan data Badan Ekonomi Kreatif, 60% UMKM kuliner di Indonesia terdampak pandemi covid. Selain itu, tingginya persaingan antar pedagang khususnya di bidang kuliner menjadikan mereka umumnya tergolong UMKM dan diharapkan mampu beradaptasi dengan keadaan tersebut dengan melakukan transformasi bisnis. Sejak pandemi Covid-19 platform yang digunakan konsumen dalam memesan platform Online Food Delivery (OFD) juga semakin populer di masyarakat. Sehingga inovasi berkelanjutan dari UMKM mendesak untuk dilakukan dan selanjutnya untuk menjaga stabilitas, informasi tentang analisis perilaku dapat membantu mengidentifikasi segmentasi konsumen yang menggunakan layanan OFD. Pengukuran diidentifikasi dari 100 konsumen OFD di Jakarta menggunakan kuesioner kemudian dianalisis menggunakan pohon keputusan. Hasil penelitian mengungkapkan terdapat lima variabel yang sangat berpengaruh terhadap belanja pembelian konsumen yaitu kesediaan membayar, frekuensi pembelian, tempat tinggal, restaurant pilihan, dan jenis restaurant. Klasifikasi pohon keputusan menunjukkan tujuh simpul dengan karakteristik konsumen yang berbeda dalam menggunakan layanan OFD. Hasil ini menunjukkan karakteristik target audiens dan klasifikasi segmentasi perilaku konsumen dalam menggunakan layanan OFD sehingga restoran dapat mempertahankan bisnis dengan melakukan inovasi yang berkelanjutan dan memanfaatkannya untuk mengetahui kebutuhan konsumen sebagai dasar pertimbangan keputusan untuk perbaikan yang lebih baik.Kata kunci: Tingkah laku, transformasi bisnis, konsumen, online food delivery (ofd), pohon keputusan